2022
DOI: 10.1007/s41109-022-00476-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the raison d’etre behind metric selection in network analysis: a systematic review

Abstract: Network analysis is a useful tool to analyse the interactions and structure of graphs that represent the relationships among entities, such as sectors within an urban system. Connecting entities in this way is vital in understanding the complexity of the modern world, and how to navigate these complexities during an event. However, the field of network analysis has grown rapidly since the 1970s to produce a vast array of available metrics that describe different graph properties. This diversity allows network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…This metric helps evaluate the complexity and interconnectedness of the network. [ 41 ] Additionally, the betweenness centrality, a measure of how often a target acts as a bridge connecting other targets in the network, [ 42 ] was calculated. The median value of the betweenness centrality was determined to be 0.003.…”
Section: Discussionmentioning
confidence: 99%
“…This metric helps evaluate the complexity and interconnectedness of the network. [ 41 ] Additionally, the betweenness centrality, a measure of how often a target acts as a bridge connecting other targets in the network, [ 42 ] was calculated. The median value of the betweenness centrality was determined to be 0.003.…”
Section: Discussionmentioning
confidence: 99%
“…SLNA was chosen because it deploys strict procedures in the search and selection of publications for a synthesis of what various studies have shown and how they have impacted policy and practice over time [19]. SLNA is also widely acknowledged for its objectivity in and suitability for identifying research trends and networks of relationships among authors, in enhancing an understanding of the current state of the research in any field and in identifying the gaps in the research, as well as areas of improvement [20].…”
Section: Source Of Data Software and Analysis Processmentioning
confidence: 99%
“…Once a system has been represented as a complex network, various measures of the network structure and organization can then be made at the micro-level to examine individual nodes, at the macro-level to examine the overall structure of the whole network, or the meso-level to examine subsets of nodes in the whole network (Morrison et al 2022). The structure of the complex network is important to understand, because the way in which a network is organized can influence processing in that system (Kleinberg 2000).…”
Section: The Network Science Perspectivementioning
confidence: 99%